PERSEPSI GURU DAN ORANG TUA TERHADAP SISTEM ZONASI DALAM PENERIMAAN PESERTADIDIK BARU PADA SMANEGERI DIKOTAKEDIRI - Kholifatul Khoiria; Raden Bambang Sumarsono; Wildan Zulkarnain; Kholifatul Khoiria; Raden Bambang Sumarsono (Universitas Negeri Malang, 2024)
Abstract: This study has several objectives, namely: (1) to determine teacher perceptions ofthe zoning system in the New Student Admissions (PPDB) in SMA Negeri KotaKediri; (2) to find out parents' perceptions of the zoning system for New StudentAdmissions (PPDB) in SMA Negeri Kota Kediri; (3) to determine differences inteacher and parent perceptions of the zoning system in the New StudentAdmissions (PPDB) in SMA Negeri Kota Kediri. The method used inthisresearch isto use a quantitative approach. The results of this study are: (1) the perception ofteachers in SMA Negeri Kediri is in the good category with a total percentage of52.24%; (2) the perceptionofparentsinSMANegeriKediri isinthe good categorywith a totalpercentage of54.17%; (3) there are differences in perceptions betweenteachers and parents regarding the zoning system in SMA Negeri Kota Kediri withthe independent t-test calculation obtained at 50.947 with a significance value of0.000